2019
DOI: 10.1021/jacs.9b02158
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistically Guided Predictive Models for Ligand and Initiator Effects in Copper-Catalyzed Atom Transfer Radical Polymerization (Cu-ATRP)

Abstract: Copper-catalyzed atom transfer radical polymerization (Cu-ATRP) is one of the most widely used controlled radical polymerization techniques. Notwithstanding the extensive mechanistic studies in the literature, the transition states of the activation/deactivation of the growing polymer chain, a key equilibrium in Cu-ATRP, have not been investigated computationally. Therefore, the understanding of the origin of ligand and initiator effects on the rates of activation/deactivation is still limited. Here, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 82 publications
3
93
0
Order By: Relevance
“…The activation of alkyl halide initiators or dormant species in ATRP by Cu I /L activators was proved to follow a concerted atom transfer inner‐sphere electron transfer pathway (ISET) . Other possible mechanisms, such as stepwise outer‐sphere electron transfer, dissociative electron transfer and oxidative addition of RX to Cu I /L via a Cu III intermediate, were found to require high energy barriers, as indicated by DFT and Marcus theory (Figure ) . Moreover, Cu I /L complexes were observed to activate RX initiators 7–10 times faster than outer‐sphere electron donors (e. g. aromatic radical anions electrochemically generated from their neutral precursors), confirming the ISET mechanism for ATRP catalysts.…”
Section: Predictive Models For the Effect Of Ligands And Initiators Omentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of alkyl halide initiators or dormant species in ATRP by Cu I /L activators was proved to follow a concerted atom transfer inner‐sphere electron transfer pathway (ISET) . Other possible mechanisms, such as stepwise outer‐sphere electron transfer, dissociative electron transfer and oxidative addition of RX to Cu I /L via a Cu III intermediate, were found to require high energy barriers, as indicated by DFT and Marcus theory (Figure ) . Moreover, Cu I /L complexes were observed to activate RX initiators 7–10 times faster than outer‐sphere electron donors (e. g. aromatic radical anions electrochemically generated from their neutral precursors), confirming the ISET mechanism for ATRP catalysts.…”
Section: Predictive Models For the Effect Of Ligands And Initiators Omentioning
confidence: 99%
“…The ISET process involves the formation of a late transition state (TS) that is structurally similar to the X−Cu II /L product . The optimized geometry of the TS for the reaction between several ATRP catalysts and ethyl α‐bromoisobutyrate (EBiB) as initiator (Figure ), revealed a bent Cu‐Br−C bond angle (140–155°).…”
Section: Predictive Models For the Effect Of Ligands And Initiators Omentioning
confidence: 99%
“…Although the size of this dataset is modest, previous studies in different elds have shown to deliver a promising predictive model with similar dataset sizes, by using models with a low complexity or by means of chemically relevant descriptors. 14,23,24…”
Section: The Datasetmentioning
confidence: 99%
“…An extensive study on the effect of the initiator in the metal‐catalyzed ATRP can be found in the research published by Tang et al [79] . Computational analysis on the role of initiator in ATRP, including the study of electronic transitions involved and an overall mechanistic understanding, can be grasped by studying different models developed by Fang et al [83] . For the photoinduced metal‐free O‐ATRP, there is a vast scope for research considering the limited number of initiators prevalent in the current literature.…”
Section: Initiatorsmentioning
confidence: 99%